The Whys of Social Exclusion : Insights from Behavioral Economics - Hoff, Karla (World Bank, Washington, DC, 2017)
All over the world, people are prevented from participating fully in society through mechanisms that go beyond the structural and institutional barriers identified by rational choice theory (poverty, exclusion by law or force, taste-based and statistical discrimination, and externalities from social networks). This essay discusses four additional mechanisms that bounded rationality can explain: (i) implicit discrimination, (ii) self-stereotyping and self-censorship, (iii) “fast thinking” adapted to underclass neighborhoods, and (iv) "adaptive preferences" in which an oppressed group views its oppression as natural or even preferred. Stable institutions have cognitive foundations -- concepts, categories, social identities, and worldviews -- that function like lenses through which individuals see themselves and the world. Abolishing or reforming a discriminatory institution may have little effect on these lenses. Groups previously discriminated against by law or policy may remain excluded through habits of the mind. Behavioral economics recognizes forces of social exclusion left out of rational choice theory, and identifies ways to overcome them. Some interventions have had very consequential impact.